THE 2016/17 PREVALENCE OF CULTURE CHANGE PRACTICE IN U.S. NURSING HOMES. (11th November 2018) - Miller, S C; Schwartz, M L; Lima, J C; Shield, R R; Tyler, D A; Berridge, C W; Lepore, M J; Clark, M A
Abstract: Using 2016/17 survey data, we estimated the national prevalence of the processes and structures promoted by the nursing home (NH) culture change movement. We administered the 2016/17 nationwide survey to 2, 142 NH administrators at NHs that previously responded to our 2009/10 survey, and the response rate was 74% (1, 584). From responses, we created index scores for the practice domains of physical environment, staff empowerment, resident-centered care, end-of-life care (a subset of resident-centered care), leadership, and family and community engagement. Indices had good internal consistency, and positive associations between index scores and quality indicators supported the criterion validity of the indices. At 82.6 (of 100), the (weighted) standardized index score for resident-centered care practices was the highest, and 76.2 for end-of-life care practices the next highest. Across all domains, there were higher domain index scores in NHs with higher leadership index scores and in states with Medicaid culture change pay-for-performance.